2018
DOI: 10.1017/s0033583518000070
|View full text |Cite
|
Sign up to set email alerts
|

Key role of the REC lobe during CRISPR–Cas9 activation by ‘sensing’, ‘regulating’, and ‘locking’ the catalytic HNH domain

Abstract: Understanding the conformational dynamics of CRISPR (clustered regularly interspaced short palindromic repeat)–Cas9 is of the utmost importance for improving its genome editing capability. Here, molecular dynamics simulations performed using Anton-2 – a specialized supercomputer capturing micro-to-millisecond biophysical events in real time and at atomic-level resolution – reveal the activation process of the endonuclease Cas9 toward DNA cleavage. Over the unbiased simulation, we observe that the spontaneous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
157
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 93 publications
(172 citation statements)
references
References 64 publications
12
157
1
Order By: Relevance
“…This resembles the reciprocal dynamical role of REC2 and HNH in Cas9, where REC2 regulates conformational changes of the catalytic HNH domain to allow TS cleavage. 19 , 23 25 In light of these observations, the dynamics of REC2 in Cas12a could assist the conformational changes of Nuc and acts as a “regulator” of its function. In support of this hypothesis, single-molecule studies of Cas12a have shown that the REC2 and Nuc domains show the largest conformational rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…This resembles the reciprocal dynamical role of REC2 and HNH in Cas9, where REC2 regulates conformational changes of the catalytic HNH domain to allow TS cleavage. 19 , 23 25 In light of these observations, the dynamics of REC2 in Cas12a could assist the conformational changes of Nuc and acts as a “regulator” of its function. In support of this hypothesis, single-molecule studies of Cas12a have shown that the REC2 and Nuc domains show the largest conformational rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…for understanding the molecular basis of the CRISPR-Cas9 function. (13)(14)(15)(16)(17) Among other studies, our group has successfully applied MD simulations to disclose a mechanism for the conformational activation of Cas9, clarifying the activation process by which the HNH domain is repositioned for cleavage in good agreement with structural and smFRET experiments. (18) Remarkably, MD simulations as well as experimental studies have indicated that the conformational changes underlying the CRISPR-Cas9 function occur over and beyond micro-to-millisecond time scales.…”
Section: Introductionmentioning
confidence: 81%
“…Specifically, the REC3 region, which directly contacts the very end of the hybrid, "senses" the formation of the DNA:RNA hybrid and allows for HNH nuclease activation. (7,13) In order to understand the role of REC3 in the hybrid recognition and in the on-target selectivity, we monitored the interactions established by the RNA:DNA hybrid with REC3 in the simulated systems. In the "unproductive" systems, we observe a significant increase of interactions between the hybrid and REC3 (separated in polar, apolar and charged contributions, Fig.…”
Section: Effect Of Off-target Binding On the Hybrid Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, DNA cleavage efficiency scales with sampling of the HNH domain conformation; a correct conformation enhances the cleavage activity of the RuvC domain 27 . This allostery between HNH and RuvC is believed to result from the hinge comprising two helices that connect RuvC-III to HNH 21,[27][28][29][30][31][32] . Mutations that disrupt one of the two hinge helices lowered the DNA cleavage activity of SpyCas9 27 .…”
mentioning
confidence: 99%